Potential value of pre- and post-therapy [68Ga]Ga-DOTA-TATE PET/CT in the prognosis of response to PRRT in disseminated neuroendocrine tumors - Opalińska, Marta; Morawiec-Sławek, Karolina; Kania-Kuc, Adrian; Al Maraih, Ibraheem; Sowa-Staszczak, Anna; Hubalewska-Dydejczyk, Alicja (Frontiers in Endocrinology, 2022)
Background Peptide receptor radionuclide therapy (PRRT) is one of the most effective therapeutic options for the treatment of metastatic, well-differentiated neuroendocrine tumors (NETs). It improves progressive disease-free survival and enables the control of hormone secretion in functioning tumors. Currently, there are no clearly established predictors of response to PRRT. The main factors hindering such a prediction are the heterogeneity of somatostatin receptor expression within and between lesions, lack of standardized parameters for functional imaging, and the use of different PRRT protocols. The main goal of our study was to quantify SUVmax changes in [68Ga]Ga-DOTA-TATE PET/CT scans as a potential predictor of long-term response to PRRT. Material and methods Out of 20 patients treated with PRRT using [177Lu]Lu and/or [177Lu]Lu/[90Y]Y-DOTA-TATE in 2017–2019 due to dissemination of neuroendocrine neoplasm, 12 patients underwent [68Ga]Ga-DOTA-TATE PET/CT on average 3.1 months before and 4.5 months after PRRT and were eligible for the analysis. In total, 76 NET lesions were evaluated. We measured SUVmax for every lesion in both PET/CT scans (before and after PRRT). Those values were corrected by liver SUVmax and liver SUVmean measured in volumetric analysis and specified as SUVlmax and SUVlmean. As a next step, changes in SUVlmax and SUVlmean were assessed based on both PET/CT scans. Finally, results were correlated with the clinical outcome assessed as progressive disease, disease stabilization, or partial response. Results The mean follow-up period was 19.9 months. Progressive disease, partial response, and disease stabilization were found in five, two, and five patients, respectively. Among patients with a partial response, the decrease in mean SUVlmax was 66.3% when compared to baseline. In patients with stable disease, the decrease in SUVlmax was 30.3% when compared to baseline. In patients with progressive disease, the mean increase in SUVlmax was 9.1% when compared to baseline. The changes in SUVlmean were -69,8%, -30.8%, and -3.7%, respectively. Conclusions A decrease in the SUVmax value in NET lesions, corrected by normal liver tissue uptake assessed in [68Ga]Ga-DOTA-TATE PET/CT scans, indicates a lower risk for NET progressive disease within 20 months after PRRT and may constitute an additional and independent parameter for the estimation of overall risk for disease progression.